Introducing the Economic Experts Survey (EES) - Klaus Gründler; Anina Harter; Martin Mosler; Niklas Potrafke; Fabian Ruthardt; Christoph Schaltegger (CESifo Forum, 2022)
The Economic Experts Survey (EES) is a newly initiated global quarterly survey of economic experts. The EES elicits the assessment of influential economic experts around the world about current economic policies and the political performance of their host countries. This article introduces the EES and presents the results from the first survey wave in the first quarter of 2022. Expert responses reveal large regional differences in the assessment of economic policy. The results further show that the overall political situation worsened compared to the previous quarter. In a special module, the EES also asks experts about their assessments of the current Covid-19 policies. Experts notice improvement in public health measures and recommend relaxing measures further compared to end-2021. They also recommend more expansionary Covid-19 fiscal policies.
Keywords: 330